Are Static and Dynamic Postural Balance Assessments Two Sides of the Same Coin? A Cross-Sectional Study in the Older Adults - Rizzato, Alex; Paoli, Antonio; Andretta, Marta; Vidorin, Francesca; Marcolin, Giuseppe (Frontiers in Physiology, 2021)
The aim of this study was to investigate if the combination of static and dynamic postural balance assessments gives more accurate indications on balance performance among healthy older adults. We also aimed at studying the effect of a dual-task condition on static and dynamic postural balance control. Fifty-seven healthy older adults (age = 73.2±5.0 yr, height = 1.66±0.08 m, body mass = 72.8±13.8 kg) completed the study. Static and dynamic balance were assessed both in single-task and dual-task conditions through a force plate and an oscillating platform. The dominant handgrip strength was also measured with a dynamometer. Pearson’s correlation revealed non-statistically significant correlations between static and dynamic balance performance. The dual-task worsened the balance performance more in the dynamic (+147.8%) than in the static (+25.10%, +43.45%, +72.93% for ellipse area, sway path and AP oscillations, respectively) condition (p < 0 .001). A weak correlation was found between dynamic balance performance and handgrip strength both in the single (p < 0.05; r = -0.264) and dual (p < 0.05; r = -0.302) task condition. The absence of correlations between static and dynamic balance performance suggests including both static and dynamic balance tests in the assessment of postural balance alterations among older adults. Since cognitive-interference tasks exacerbated the degradation of the postural control performance, also dual-task condition should be considered in the postural balance assessment.